TRANSFORMASI BERPIKIR GEOMETRI KELAS 5 SD MELALUI MEDIA VR DI MUSEUM HOUSE OF SAMPOERNA - Intan Pratiwi, Novia Ayu; Feny Rita Fiantika; Prayogo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the transformation of geometric thinking of 5th grade elementary school students in solving spatial problems using virtual reality media. This type of research is descriptive qualitative with an exploratory approach method. The data collection technique uses interviews, written tests, observations and documentation. The results of this study indicate a significant increase in the learning outcomes of 5th grade students of SDN Dr. Sutomo V/327 Surabaya in the subject of mathematics on spatial geometry.